PENGGUNAAN MEDIA YOU TUBE UNTUK MENINGKATKAN HASIL BELAJAR SISWA POKOK BAHASAN SISTEM PENCERNAAN MAKANAN PADA MANUSIA KELAS VIII DI MTs SA MIFTAHUS SAADAH SUKORAMBI JEMBER TAHUN PELAJARAN 2017/2018 - Siti Kholifah; Siti Roudlotul Hikamah; Haning Hasbiyati (JURNAL BIOSHELL, 2018)
Learning is a principal activity of education process. Researchers conducted observations in class VIII MTs SA Miftahus Saadah Sukorambi and obtained data around 85% which shows student score  70. This research aimed to determine the Increasing of Student study Results in studying the digestive system of humans by youtube media. The Type of the research used is a classroom action research (CAR). The procedure used is the cycle model. Based on reseach results,  The percentage of student learning result in cycle I is 75% and a cycle II is 85%. The result of daily test of the student in cycle I is 78,85. While in the cycle II  is 86,65. This case shows that the result of student learning can increase by you tube media for certain main idea. You Tube media is used to avoid the saturation in learning prosses.Keywords: The using of YouTube media, Reasult of student learning,